Exploring The Lived Experience in Literacy, Language, and Cultural Navigations of International Student in Indonesia - Khairunnisa, Fathia; Silvhiany, Sary; Vianty, Machdalena (Universitas Pendidikan Ganesha, 2025)
International student faced unique challenges in adapting to a new language and linguistic environment. The language difficulties faced by students impact their ability to understand learning materials. This study aims to analyze the literacy practices of international students from Tajikistan studying in Indonesia that have developed over time and what role language proficiency and cultural context play in shaping literacy development during the academic journey. This type of research is qualitative, using a qualitative narrative approach. This study explores the lived experiences of Tajik students in the Indonesian academic environment. The subjects of this study were Tajik students. Data collection mainly consisted of semi-structured interviews conducted face-to-face. The data collection instrument was an interview sheet. The data analysis method applied was thematic analysis following Creswell's six steps of data analysis. The research findings revealed that language barriers initially hampered academic adaptation and social integration. However, peer support, informal learning strategies, and extracurricular participation emerged as necessary in overcoming this challenge. Students gradually developed language proficiency, shifting from relying on their mother tongue to engaging confidently in Bahasa Indonesia. This study highlights the importance of immersive learning experiences, including social interactions and institutional support, in fostering academic success and intercultural competence.